Net Working Capital and Firm Growth - Abuhommous, Alaa Adden A. (International Review of Management and Marketing, 2017)
There are many empirical studies that have analyzed firms' growth; however, there has not been a direct examination of the relationship between working capital management and firm growth. Thus, this study examines the effect of the working capital level on the growth of firms from a sample of Jordanian firms; the data are unbalanced data for the period from 1999 to 2015. The study extends the literature on firm growth and finds evidence that investment in working capital has a positive effect on firm growth. The paper also shows that young and small firms grow more than mature and large firms. Moreover, we find that a high level of internal cash flow decreases a firm's growth. We also find a positive relationship between the market expectation and market-based financial performance and firm growth. Keywords: Finance, Investment, Firm Growth, Net Working Capital JEL Classifications: L25, L11